Невичерпні можливості добору на прикладі посівних конопель - Вировець, В.Г.; Лайко, І.М.; Кириченко, Г.І.; Горшкова, Л.М. (Фактори експериментальної еволюції організмів, 2013)
Aims. To increase fiber yield by the way of it’s increasing in stems. Methods. Family-group selection of the highest fiber content plants by the stems evaluation by direct signs. Results. At first three years exceeding of fiber content in breeding material in comparison with initial variety was 0,2; 0,5 and 0,6 % and in last – 1984 and 1985 – 19,6 and 19,3 %. So in 40 years the fiber content is 34,8 %. It increased almost at 2,5 times. Conclusions. As a result of purposeful selection the main population was created in which the form-forming process is passing and assisting for appearance of new high fiber content plants.